Existence of Solutions to the Variable Order Caputo Fractional Thermistor Problem - John R. Graef; Kadda Maazouz; Sandra Pinelas; Zineb Bellabes; Naima Boussekkine (Fractal and Fractional)
The thermistor model captures the complex interaction between heat dissipation, electrical current conduction, and Joule heat generation. Our research examines the diverse properties and implications of employing fractional calculus in the analysis with a focus on fixed-point principles. This paper addresses the existence and uniqueness of solutions to a variable order Caputo fractional thermistor problem by applying Schauder’s fixed-point theorem.